2003
DOI: 10.1093/ps/82.8.1235
|View full text |Cite
|
Sign up to set email alerts
|

Early age thermal conditioning immediately reduces body temperature of broiler chicks in a tropical environment

Abstract: Early age thermal conditioning (TC) durably improves resistance of broilers to heat stress and reduces body temperature (Tb). Three experiments on broiler chicks were conducted to evaluate the effects of TC at 5 d of age on Tb variation measured by thermometer between 4 and 7 d of age, under a tropical environment. Because manipulation of chickens to measure Tb with a thermometer may increase Tb, a preliminary experiment on 13 3-to-4-wk-old male broilers compared Tb measured by telemetry to Tb measured in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 26 publications
4
24
0
7
Order By: Relevance
“…In the three experiments, Tb at 7 days of age was reduced by TC as described earlier [11,12] and this reduction remained consistent until the end of the production period, in agreement with earlier findings [3,26,28]. Recent results showed that TC induces the stimulation of gut development and activity, reduces the circulating level of T3 and increases feed intake during the 48 hours following TC [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the three experiments, Tb at 7 days of age was reduced by TC as described earlier [11,12] and this reduction remained consistent until the end of the production period, in agreement with earlier findings [3,26,28]. Recent results showed that TC induces the stimulation of gut development and activity, reduces the circulating level of T3 and increases feed intake during the 48 hours following TC [25].…”
Section: Discussionsupporting
confidence: 91%
“…Optimal penetration according to the size of the chickens and timing were determined by preliminary trials. Simultaneous telemetry recordings confirmed that Tb was not affected by the manipulation of the chickens [12]. Tb was measured in all chicks at 4 and 7 days of age, i.e.…”
Section: Measurementsmentioning
confidence: 53%
“…Furthermore, the body temperature of chicks exposed to 38°C at 5 day posthatch remained significantly lower than that of controls up to 40 days in tropical conditions . Body temperature was shown to be an accurate indicator of thermotolerance of endotherms under a wide range of ambient temperatures, including chickens during their life span (De Basilio et al, 2003): chickens that died during heat challenge at 34 day had higher body temperatures (+0.6°C)…”
Section: Early Tm Of Poultry Speciesmentioning
confidence: 99%
“…Although postnatal TM seems to be an interesting technique, there are limitations to applying it on a large scale because of the difficulties of maintaining 38°C homogeneously for 24 h in the poultry house. It depends on the type and efficacy of the heat source (De Basilio et al, 2003) and on the poultry house insulation. TM during embryogenesis, performed directly in incubators, may therefore be easier for the poultry industry to apply.…”
Section: Early Tm Of Poultry Speciesmentioning
confidence: 99%
“…The age for the thermal conditioning applied in this study was referred to the previous reports (De Basilio et al, 2001Basilio et al, , 2003. Thereafter, treatment chicks were exposed to high temperature at 40℃ for 3 h while control chicks were kept at 30℃.…”
Section: Experimental Designmentioning
confidence: 99%